Media Effectiveness Health Promotion Video and Poster on Covid-19 Vaccination on Improving Knowledge and Attitude of Cadres in Banda Aceh City - Nurul Fajri; Said Usman; Sofia Sofia; Irwan Saputra; Marthoenis Marthoenis (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The COVID-19 pandemic since March 2020 until now has had an impact on all aspects of people's lives. The government has made various efforts to achieve the COVID-19 vaccination target, but promotive and preventive efforts still need to be strengthened considering that many people refuse vaccination. In Indonesia, promotional efforts using video and poster media have begun to develop. Puskesmas is a health service facility that focuses on promotive efforts where the involvement of health cadres greatly influences these efforts. The purpose of the study was to determine the effectiveness of video and poster health promotion media on increasing the knowledge and attitudes of cadres about COVID-19 vaccination. Research methods:Method usedRandomized Controlled Trialpretest posttest with control group design.The population is all health cadres in Banda Aceh City. Randomly selected at the cluster level. Of the 9 sub-districts, 3 sub-districts were selected as the population to be studied. Sampling by Cluster Randomized Sampling based on the sampling criteria, the determination of the sample size using OpenEpi software is 213 people. Data retrieval using a questionnaire was analyzed by Kruskal Wallis statistical test with Post hoc Mann Whitney, Wilcoxon, Spearmen's Bivariate Correlation and Multivariate Multiple Linear Regression. Research result:. video and poster media were effective in increasing the knowledge and attitudes of cadres (P=.000) and there was no difference in their effectiveness (P=.212 and P=.228).The level of knowledge and attitudes of cadres increased after being given an intervention with video and poster media (P=.000). There was no effect of the Confounding variable on the level of knowledge and attitudes of cadres (age P = ,122 and ,438), (education P = 089 and ,308), (occupation P = ,445 and ,163), (service period P = ,051 and .264), (vaccination training P=.16 and .18) (income P=.265 and .412). The most dominant variables influencing the level of knowledge and attitudes of cadres are video media and poster media (P=.000 and P=.001).